International myeloma working group (IMWG) consensus statement and guidelines regarding the current status of stem cell collection and high-dose therapy for multiple myeloma and the role of plerixafor (AMD 3100) - Giralt, S.; Stadtmauer, E.A.; Harousseau, J.L.; Palumbo, A.; Bensinger, W.; Comenzo, R.L.; Kumar, S.; Munshi, N.C.; Dispenzieri, A.; Kyle, R.; Merlini, G.; San Miguel, J.; et al. (Leukemia, 2009)
Multiple myeloma is the most common indication for high-dose chemotherapy with autologous stem cell support (ASCT) in North America today. Stem cell procurement for ASCT has most commonly been performed with stem cell mobilization using colony-stimulating factors with or without prior chemotherapy. The target CD34+ cell dose to be collected as well as the number of apheresis performed varies throughout the country, but a minimum of 2 million CD34+ cells/kg has been traditionally used for the support of one cycle of high-dose therapy. With the advent of plerixafor (AMD3100) (a novel stem cell mobilization agent), it is pertinent to review the current status of stem cell mobilization for myeloma as well as the role of autologous stem cell transplantation in this disease. On June 1, 2008, a panel of experts was convened by the International Myeloma Foundation to address issues regarding stem cell mobilization and autologous transplantation in myeloma in the context of new therapies. The panel was asked to discuss a variety of issues regarding stem cell collection and transplantation in myeloma especially with the arrival of plerixafor. Herein, is a summary of their deliberations and conclusions.